2018
DOI: 10.21037/jtd.2018.05.74
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between laryngeal mask airway and endotracheal intubation for anaesthesia in adult patients undergoing NUSS procedure

Abstract: Compared with ETT, the application of LMA for general anaesthesia may demonstrate promising advantages in airway management for the VATS-NUSS procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 14 publications
(15 reference statements)
4
26
0
Order By: Relevance
“…The LMA has many advantages over the ETT, such as having no direct contact with the tracheal mucosa, no need for direct laryngoscopy during inserting, and less adverse events such as lower frequency of coughing and decreased oxygen saturation during emergence, and lower incidence of sore throat in adults [ 6 ]. In recent years, new generation SADs have been developed, such as LMA-Supreme™, which is more superior than LMA-Classic with respect to safety of airway management [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LMA has many advantages over the ETT, such as having no direct contact with the tracheal mucosa, no need for direct laryngoscopy during inserting, and less adverse events such as lower frequency of coughing and decreased oxygen saturation during emergence, and lower incidence of sore throat in adults [ 6 ]. In recent years, new generation SADs have been developed, such as LMA-Supreme™, which is more superior than LMA-Classic with respect to safety of airway management [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The basic characteristics of the included studies A total of 14 RCTs were included in the study according to the PRISMA guidelines (shown in Figure 1), including 1,426 patients, with 707 patients in the non-intubated group and 719 patients in the intubated group (Table 1). As shown in Table 1, based on the Jadad scale, eight studies were of good quality (18,19,(21)(22)(23)25,29,30) with scores of 3 or above. The types of surgery in these reports are mostly classified as thoracoscopic operations.…”
Section: Search Resultsmentioning
confidence: 99%
“…Bullectomy (17,19,24), wedge resection (23), sympathectomy (18), talc pleurodesis (26), and pleural biopsy (20) are defined as minor thoracic surgery. Nuss surgery (22) and lung volume reduction surgery (25) are defined as moderate thoracic surgery. Lobectomy and segmentectomy (30) are defined as major thoracic surgery.…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, vagus nerve dominance and slow heart rate during spinal anesthesia may also result in significant hemodynamic variations. On the contrary, general anesthesia with LMA and nerve block has been shown to have less effect on hemodynamics [5,11,12].…”
Section: Discussionmentioning
confidence: 99%